The Impact of Nutrition and Intestinal Microbiome on Elderly Depression-A Systematic Review - Klimova, Blanka; Novotny, Michal; Valis, Martin (Nutrients, 2020)
The aim of this review is to systematically review the evidence whether proper nutrition has a positive impact on the prevention or decline of depressive symptoms among elderly people. In addition, possible connections between nutrition, microbiome, and serotonin molecules and its tryptophan precursor are discussed. The methodology follows the PRISMA guidelines, including the PRISMA flow chart. The authors systematically reviewed peer-review, English-written articles published in Web of Science and PubMed between 2013 and 2018. The findings of six original articles, detected on the set inclusion and exclusion criteria, indicate that there is an association between nutrition and depressive symptoms in the target group, i.e., that proper nutrition has a positive impact on the prevention or reduction of depressive symptoms among elderly people. The findings also reveal that there is a considerable correlation between the intakes of vitamin B and a decrease in the prevalence of depressive symptoms. Furthermore, sufficient nutrient intake of tryptophan appears to be an important factor in terms of nutrition and serotonin levels in the body. The authors consider it important to explore associations between the overall dietary intake and depression since diets are not consumed as individual nutrients. Returning to preventive approaches seems to be a rational way to promote the mental health of seniors. Future studies thus need to include interdisciplinary collaboration: from a good diagnosis of the disease by a psychiatrist, through an analysis of the need for nutrient metabolism by a biochemist to the development of a nutritional plan by a nutritional therapist. The limitations of this review consist in a relatively small number of the studies on this topic, including just few randomized controlled trials, which are a guarantee of efficacy and objectivity in comparison with cross-sectional studies.
Keywords: elderly; vitamin B komplex; Vitamin B Complex; Female; Age Factors; ženské pohlaví; Gastrointestinal Microbiome; Serotonin; nutriční terapie; věkové faktory; Nutritional Status; lidé; serotonin; gut-brain axis; tryptofan; Nutrition Therapy; Aged, 80 and over; depression; nutriční stav; Elder Nutritional Physiological Phenomena; fyziologie výživy seniorů; microbiome; Male; Aged; střevní mikroflóra; nutrition; vitamin; Tryptophan; tryptophan; deprese; senioři nad 80 let; senioři; mužské pohlaví; Depression; Humans